Drug‐induced interstitial pneumonia after intravesical Bacillus Calmette‐Guerin administration for bladder cancer with scleroderma. Issue 2 (24th January 2023) - Yoshioka, Fumie; Kato, Taigo; Shima, Yoshihito; Hatano, Koji; Kawashima, Atsunari; Fukuhara, Shinichiro; Imamura, Ryoichi; Nonomura, Norio
Abstract : Introduction: Intravesical Bacillus Calmette‐Guerin administration is the standard therapy for high‐risk nonmuscle invasive bladder cancer and is usually well tolerated. However, some patients experience severe, potentially fatal, complications including interstitial pneumonitis. Case presentation: A 72‐year‐old female with scleroderma was diagnosed with bladder carcinoma in situ. She developed severe interstitial pneumonitis with the first administration of intravesical Bacillus Calmette‐Guerin after the cessation of immunosuppressive agents. Six days after the first administration, she experienced dyspnea at rest, and computed tomography revealed scattered frosted shadows in the upper lung. The following day, she required intubation. We suspected drug‐induced interstitial pneumonia and started steroid pulse therapy for 3 days, resulting in a complete response. No exacerbation of scleroderma symptoms or recurrence of cancer was observed 9 months after Bacillus Calmette‐Guerin therapy. Conclusion: For patients receiving intravesical Bacillus Calmette‐Guerin therapy, close observation of the respiratory condition is necessary for early therapeutic intervention.